The Holocaust and Germanization of Ukraine - Steinhart, Eric Conrad (Publications of the German Historical Institute, 2015)
"The German invasion of the Soviet Union during the Second World War was central to Nazi plans for territorial expansion and genocidal demographic revolution. To create "living space," Nazi Germany pursued two policies. The first was the systematic murder of millions of Jews, Slavs, Roma, and other groups that the Nazis found undesirable on racial, religious, ethnic, ideological, hereditary, or behavioral grounds"--